The influence of Trust on Continuance Intention of the Tokopedia Application is mediated by Perceived Risk and Perceived Benefits for Padang City Consumers - Nofzil, Fellina Putri; ., Firman (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2024)
The aim of this research is to analyze (1) the influence of trust on the continuance intention of Tokopedia users in Padang City. (2) the influence of trust on the perceived risk of Tokopedia users in Padang City. (3) the influence of trust on the perceived benefits of Tokopedia users in Padang City. (4) the influence of perceived risk on the continuance intention of Tokopedia users in Padang City. (5) the influence of perceived benefit on the continuance intention of Tokopedia users in Padang City. (6) the influence of trust on the continuance intention of Tokopedia users in Padang City with perceived risk as a mediating variable. (7) the influence of trust on the continuance intention of Tokopedia users in Padang City with perceived benefit as a mediating variable. This type of research is quantitative descriptive research, the number of samples in this research is 180 respondents using purposive sampling techniques, the data analysis method uses SEM analysis using the Smart application. The results of the research are 1) there is a significant influence between trust on the continuance intention of Tokopedia users in Padang City . (2) there is a significant influence between trust on the perceived risk of Tokopedia users in Padang City. (3) there is a significant influence between trust on the perceived benefits of Tokopedia users in Padang City. (4) there is a significant influence between perceived risk on the continuance intention of Tokopedia users in Padang City. (5) there is a significant influence between perceived benefit on the continuance intention of Tokopedia users in Padang City. (6) there is a significant influence between trust on the continuance intention of Tokopedia users in Padang City with perceived risk as a mediating variable. (7) there is a significant influence between trust on the continuance intention of Tokopedia users in Padang City with perceived benefit as a mediating variable.